Muscular system the inner athlete (New Jersey : Cambridge Educational, 1998)
This program looks at the many roles played by muscle and skin in our everyday lives. Topics include muscles and movement; cardiac, smooth, and skeletal muscle contraction and movement; muscles and posture; homeostasis; and the important roles played by skin, hair, nails, and glands
Keywords: Musculoskeletal System; Movement